PERBANDINGAN LAMA WAKTU PENUNDAAN SPESIMEN FESES TERHADAP PEMERIKSAAN SOIL TRANSMITTED HELMINTH DENGAN METODE KATO−KATZ - Jenita Nurrafikasari, Putri; Sulaeman; Sundara Mulia, Yuliansyah; Kurniawan, Entuy (Politeknik Kesehatan Kemenkes Bandung, 2024)
Soil transmitted helminth (STH) is a parasitic worm whose spread requires soil media. The spesieses of STH that infect humans are Ascaris lumbricoides, Trichuris trichiura, Necator americanus, and Ancylostoma duodenale. The Kato-katz method is easy to perform but requires accuracy in counting the number of worm eggs. The number of worm eggs found can be influenced by the length of time the sample is delayed. This research aims to determine the difference in the number of STH eggs based on the length of time delayed fresh feces samples in less than 3 hours and delayed feces samples less than 72 hours using the Kato-katz method. The research was conducted with feces samples from Padjadjaran University which indicated the presence of STH eggs. The results found in the delayed feces samples < 72 hours eggs are less than in fresh feces samples in < 3 hours. The number of Ascaris lumbricoides eggs in fresh samples in < 3 hours was 4,950 EPG while in samples delayed < 72 hours was 3,495 EPG. The number of Trichuris trichiura eggs in fresh samples in < 3 hours was 510 EPG while in samples delayed < 72 hours was 450 EPG. Based on Twoway Anova test obtained sig value. < 0.05 from the time delay to the results of the eggs found, namely 0.037. So, it can be interpreted that there is an influence in the length of time delayed examination of feces samples on the number of Soil transmitted helminth eggs found.